2016
DOI: 10.1159/000449509
|View full text |Cite
|
Sign up to set email alerts
|

Different Training-Induced Skeletal Muscle Adaptations in COPD Patients with and without Alpha-1 Antitrypsin Deficiency

Abstract: Background: Pulmonary rehabilitation (PR) improves oxidative capacity of peripheral muscles in patients with chronic obstructive pulmonary disease (COPD). The exercise-induced oxidative skeletal muscle adaptation in COPD patients with inherited alpha-1 antitrypsin deficiency (A1ATD) has not been studied. Objectives: To compare PR effects on skeletal muscle adaptation in COPD patients with and without A1ATD. Methods: Nine COPD patients with A1ATD (genotype PiZZ, 6 receiving A1AT augmentation therapy), and 10 ‘u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…Recently, an unfavorable muscle response to exercise has been shown in a small number of AATD patients, compared with usual COPD,90 suggesting that evidence about PR might not be wholly generalizable to AATD either. This is backed up by a study of a 5-week PR program pretransplantation, where AATD patients were observed to have a smaller improvement in 6-min walking test distance compared with usual COPD (47.9 vs 60.6 m) 91.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an unfavorable muscle response to exercise has been shown in a small number of AATD patients, compared with usual COPD,90 suggesting that evidence about PR might not be wholly generalizable to AATD either. This is backed up by a study of a 5-week PR program pretransplantation, where AATD patients were observed to have a smaller improvement in 6-min walking test distance compared with usual COPD (47.9 vs 60.6 m) 91.…”
Section: Discussionmentioning
confidence: 99%
“…Im Hinblick auf die optimale Dauer und Trainingsfrequenz einer pulmonalen Rehabilitation besteht im internationalen Schrifttum kein Konsens [40]. Bei den COPD-Patienten deuten zumindest erste Biopsiedaten eine messbare Strukturverbesserung der Muskulatur bereits nach 3-wöchiger Trainingsphase an [41]. Prinzipiell steigt die Wirksamkeit der pneumologischen Rehabilitation mit dessen Dauer an.…”
Section: Dauer Der Rehabilitationunclassified
“…Although the Nrf2-dependent antioxidant response in skeletal muscle decreases with age (Done et al, 2016; Sachdeva et al, 2014), exercise training induces expression of two Nrf2 target genes, namely mitochondrial transcription factor (TFAM) and nuclear respiratory factor 1 (NRF-1) in mouse skeletal muscle (Merry and Ristow, 2016). Pulmonary rehabilitation exercises improve the adaptation of oxidative phosphorylation in skeletal muscles in patients with chronic obstructive pulmonary disease via induction of TFAM and PGC1α (Jarosch et al, 2016). The report of Jarosch et al (2016) and many others highlight the fact that mitochondrial signaling plays a functional role in promoting exercise efficiency.…”
Section: Muscle Metabolism In Agingmentioning
confidence: 99%
“…Pulmonary rehabilitation exercises improve the adaptation of oxidative phosphorylation in skeletal muscles in patients with chronic obstructive pulmonary disease via induction of TFAM and PGC1α (Jarosch et al, 2016). The report of Jarosch et al (2016) and many others highlight the fact that mitochondrial signaling plays a functional role in promoting exercise efficiency. Both NRF-1 and PGC1α stimulate human telomere transcription in response to exercise via AMPK activation, connecting telomere protection in aging with metabolism (Diman et al, 2016).…”
Section: Muscle Metabolism In Agingmentioning
confidence: 99%